Temporal and spatial transcriptomic and microRNA dynamics of CAM photosynthesis in pineapple. (21st August 2017) - Wai, Ching M.; VanBuren, Robert; Zhang, Jisen; Huang, Lixian; Miao, Wenjing; Edger, Patrick P.; Yim, Won C.; Priest, Henry D.; Meyers, Blake C.; Mockler, Todd; Smith, J. Andrew C.; Cushman, John C.; et al.
Summary: The altered carbon assimilation pathway of crassulacean acid metabolism (CAM) photosynthesis results in an up to 80% higher water‐use efficiency than C3 photosynthesis in plants making it a potentially useful pathway for engineering crop plants with improved drought tolerance. Here we surveyed detailed temporal (diel time course) and spatial (across a leaf gradient) gene and microRNA (miRNA) expression patterns in the obligate CAM plant pineapple [ Ananas comosus (L.) Merr.]. The high‐resolution transcriptome atlas allowed us to distinguish between CAM‐related and non‐CAM gene copies. A differential gene co‐expression network across green and white leaf diel datasets identified genes with circadian oscillation, CAM‐related functions, and source‐sink relations. Gene co‐expression clusters containing CAM pathway genes are enriched with clock‐associated cis ‐elements, suggesting circadian regulation of CAM. About 20% of pineapple microRNAs have diel expression patterns, with several that target key CAM‐related genes. Expression and physiology data provide a model for CAM‐specific carbohydrate flux and long‐distance hexose transport. Together these resources provide a list of candidate genes for targeted engineering of CAM into C3 photosynthesis crop species. Significance Statement: The CAM pathway represents a potentially viable option for engineering improved drought tolerance and water‐use efficiency in crop plants. Central to the success of this approach is a systems level understanding of the underlying pathways regulating CAM. Here we surveyed detailed temporal (diel time course) and spatial (across a leaf gradient) gene and miRNA expression patterns in the obligate CAM plant pineapple ( Ananas comosus ). Together these resources provide a model for CAM regulation, carbohydrate flux, and source‐sink relations.